Identification of Physical Condition and Anthropometrics of Women's Volleyball Athletes Central Sulawesi - Kungku, Christian; Liloi, Delvi Kristanti; Sardiman, Sardiman (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective. of the study was to assess the physical and anthropometric conditions of female volleyball athletes in Central Sulawesi. This research is a descriptive study employing a quantitative methodology. Materials and Methods. The study population comprised 14 volleyball athletes from Central Sulawesi PON. The sample method employed was Purposive sample. The data collection technique employed the TEST and measurement methodologies. The instruments employed to assess physical conditions in this study included: 1) speed (30-meter run), 2) arm muscle strength, 3) explosive power (vertical leap), 4) flexibility (sit and reach), 5) agility (shuttle run 4x10m), and 6) endurance (1600m run). Results. The study results, derived from physical condition tests conducted on 14 volleyball participants in Central Sulawesi Province, yielded the following findings. There were no athletes (0) or 0% in the very good category, 3 athletes or 21.43% in the good category, 11 athletes or 78.57% in the moderate category, and no athletes in the less and very less categories (0) or 0%. The anthropometric measures yielded an average weight of 59.14 kg, a minimum weight of 56 kg, and a maximum weight of 63 kg. Mean height is 169.21 cm, with a low of 154 cm and a maximum of 176 cm. Mean leg length is 72.57 cm, with a minimum of 69 cm and a maximum of 78 cm. Mean arm spread is 35.79 cm, with a minimum of 32 cm and a maximum of 40 cm. Conclusion. The physical condition of female volleyball athletes in Central Sulawesi Province during PON is, on average, categorized as medium.